2011
DOI: 10.1089/acm.2010.0120
|View full text |Cite
|
Sign up to set email alerts
|

High-Velocity Insertion of Acupuncture Needle Is Related to Lower Level of Pain

Abstract: These results suggest that needle insertion velocity might be a factor for controlling inadvertent pain during the acupuncture needling process and that biomechanical properties of needling may be related to acupuncture perception or sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For example, the number of treatment sessions ranged from 1 to 20 and the duration of each session from 15 to 30 min across the included trials. These variations in acupuncture technique and treatment dosage may impact outcomes 8 , 9 and are thus important to consider in interpreting the results of this review and discussing their clinical implications.…”
Section: Summary Of Acupuncture and Control Proceduresmentioning
confidence: 99%
“…For example, the number of treatment sessions ranged from 1 to 20 and the duration of each session from 15 to 30 min across the included trials. These variations in acupuncture technique and treatment dosage may impact outcomes 8 , 9 and are thus important to consider in interpreting the results of this review and discussing their clinical implications.…”
Section: Summary Of Acupuncture and Control Proceduresmentioning
confidence: 99%
“…At these angle limits where the needle is nearly perpendicular to the skin surface, the insertion length and the insertion depth can be used interchangeably. This training is essential because a safe insertion with a high speed can reduce pain in body acupuncture [32,33]. This…”
Section: Validationmentioning
confidence: 99%
“…For instance, the needling sensation caused by lifting-thrusting is usually stronger than that of twirling ( Huang et al, 2012 ), whereas twirling may further improve the patient’s pressure pain threshold ( Choi et al, 2013 ). Meanwhile, even with the same acupuncture manipulation, some studies found that a better analgesic effect could be achieved by greater needling velocity ( Yin et al, 2011 ) or amplitude ( Itoh et al, 2011 ). In addition, the persistence of such sensation and pain-relieving effects is also based on a certain time of stimulation.…”
Section: Introductionmentioning
confidence: 99%